Oligomeric self-assembly hole transport layer material and preparation method and application thereof
Through the preparation of oligomerized self-assembled hole transport layer materials, the problems of existing materials consistency and complex synthesis are solved, the photoelectric conversion efficiency and stability of organic solar cells are improved, and the high coverage rate and efficient hole transport of materials are achieved.
Patent Information
- Application Number
- CN202510878706.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-09-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polymer and small molecule hole transport layer materials have poor batch consistency, complex synthesis, and cumbersome purification process, resulting in unstable performance of organic solar cells and poor coverage.
Oligomerized self-assembled hole transport layer material is used to connect oligomerized organic compounds with specific structures to aromatic groups, combine Suzuki coupling reaction and trimethyl bromide silane reaction to prepare a hole transport layer material with a unique structure, improving the binding strength and hole transport performance with ITO transparent conductive glass.
The hole transport layer material with low cost and good batch consistency is achieved, which improves the photoelectric conversion efficiency and stability of organic solar cells, and enhances the coverage and hole transport efficiency of the material on the substrate.
Smart Images

Figure CN120574259A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic photoelectric materials, and in particular relates to an oligomeric self-assembled hole transport layer material and a preparation method and application thereof. Background Art
[0002] As a clean, renewable energy source, the development and utilization of solar energy has become a key direction in the global energy transition. Accelerating energy structure adjustments, particularly in the renewable energy sector, have brought unprecedented development opportunities to the solar cell industry.
[0003] Organic solar cells, with their low cost, lightweight, ultra-thin, flexible, and easy large-area fabrication advantages, hold broad application prospects in portable, flexible batteries, and photovoltaic building energy supply. In recent years, the photoelectric conversion efficiency of organic solar cells has significantly improved, currently reaching 20.8%, demonstrating enormous potential for commercial application.
[0004] The hole transport layer plays the role of transporting holes to the contact electrode and blocking the reverse transport of electrons and reducing recombination in the device. For the existing polymer hole transport layer materials, there are differences between batches, which will lead to inconsistency in device performance, and the synthesis may involve a complex purification process; for the existing small molecule hole transport layer materials, their hole transport performance is particularly sensitive to layer thickness and coverage, which can easily lead to multi-layer stacking and poor coverage. In view of this, the technical problem to be solved by the present invention is to provide a method for preparing oligomeric self-assembled hole transport layer materials with low cost, consistency between batches, simple post-processing, and simple purification process. The improvement of these materials will make up for the defects of existing materials and help improve the photoelectric conversion efficiency of organic solar cells. Summary of the Invention
[0005] The purpose of the present invention is to provide an oligomeric self-assembled hole transport layer material and its preparation method and application, so as to solve the above-mentioned technical problems.
[0006] To achieve the above objectives, the specific technical solution of the oligomeric self-assembled hole transport layer material of the present invention is as follows:
[0007] An oligomeric self-assembled hole transport layer material comprises an oligomeric organic compound having a general structure of formula (I) or formula (II):
[0008]
[0009] In formula (I) and formula (II), n is an integer selected from 0 to 5, and R is a structure including an aromatic group.
[0010] The R is one of the following three general structures:
[0011]
[0012] The present invention also provides a method for preparing an oligomeric self-assembled hole transport layer material, comprising the following steps:
[0013] 1) Under inert gas protection, 3-halogen carbazole is dissolved in an organic solvent, ice-bathed at 0°C, and then NaH is added. Then, a phosphonate with a halogen end group is added, and the mixture is heated under reflux. After extraction and column chromatography, a solid product is obtained;
[0014] 2) Under inert gas protection and in an alkaline environment, mixing the product obtained in step 1) with an aryl borate, adding an organic solvent and a catalyst, heating under reflux to perform a Suzuki coupling reaction, and obtaining a carbazole phosphonate benzene derivative through extraction and column chromatography;
[0015] 3) Under inert gas protection, dissolving the product obtained in step 2) in an organic solvent, adding trimethylsilyl bromide to react at room temperature, quenching with alcohol, and then precipitating with a poor solvent. The precipitated solid is filtered to obtain the oligomeric self-assembled hole transport layer material.
[0016] The general reaction formula is as follows:
[0017]
[0018] or
[0019]
[0020] Wherein: X is selected from F, Cl or Br, preferably Br; n is selected from an integer of 0-5.
[0021] Furthermore, in step 1), the organic solvent is one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), etc.; the molar ratio of 3-halogen carbazole to phosphonate with a halogen end group is 1:1-3; the molar ratio of 3-halogen carbazole to NaH is 1:1-3; the reaction temperature for heating and reflux is 60°C-100°C, and the reaction time is 12-24h.
[0022] Furthermore, in step 2), the organic solvent is toluene or toluene:ethylene glycol dimethyl ether = 1:1 (V / V). The catalyst is a metal catalyst, which is one or more of tetrakistriphenylphosphine palladium, palladium acetate, di(tri-tert-butylphosphine) palladium, tris(dibenzylideneacetone)dipalladium, methanesulfonic acid (2-dicyclohexylphosphine 2', 4', 6'triisopropyl 1, 1'biphenyl) (2'amino 1, 1'biphenyl 2-yl) palladium, etc.; the alkaline environment is achieved by adding one or more of cesium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, etc.; the molar ratio of the product obtained in step 1) to the aryl borate is 2 to 4:1; the reaction temperature for heating and reflux is 110°C to 125°C; and the reaction time is 12 to 24 hours. Further preferably, step 2) is carried out under the catalysis of tetrakistriphenylphosphine palladium for the Suzuki coupling reaction.
[0023] Furthermore, in step 3), the organic solvent is one or more of 1,4-dioxane, dichloromethane, and dimethyl sulfoxide (DMSO); the molar ratio of the product obtained in step 2) to trimethylsilyl bromide is 1:5 to 1:100. The reaction temperature is room temperature, and the reaction time is 12 to 24 hours.
[0024] The present invention also provides an application of an oligomeric self-assembled hole transport layer material in the preparation of a photoelectric functional device, wherein the photoelectric functional device is an organic solar cell; the structure of the organic solar cell device is, from bottom to top, ITO transparent conductive glass, hole transport layer, active layer, electron transport layer, metal electrode, and the hole transport layer includes the oligomeric self-assembled hole transport layer material.
[0025] The present invention has the following advantages:
[0026] 1. The present invention provides a novel oligomeric self-assembled hole transport layer material having a unique structure with an aromatic di-site group as the core and connecting two phosphonic acid alkyl carbazole units.
[0027] 2. The present invention also provides a method for preparing the oligomeric self-assembled hole transport layer material. The entire preparation process is easy and the purification is simple, the yield is high, and the batch-to-batch consistency is achieved.
[0028] The oligomeric self-assembled hole transport layer material provided by the present invention, due to its bisphosphonic acid groups, can enhance its bonding strength with ITO transparent conductive glass and increase its coverage, thereby improving the material's wettability on the substrate. Furthermore, it possesses a larger π-conjugated system, which facilitates hole transport, allowing holes in the active layer to more easily pass through the hole transport layer material to the ITO transparent conductive glass. Ultimately, this improves the efficiency and stability of battery devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1is a schematic structural diagram of an organic solar cell according to the present invention;
[0030] Figure 2 The structural formula of 2PACZ, a comparative hole transport layer material used in the organic solar cell of the present invention;
[0031] Figure 3 Structural formula of PM6, the active layer donor material used in organic solar cells;
[0032] Figure 4 The structural formula of L8-BO, an active layer acceptor material used in organic solar cells;
[0033] Figure 5 The structural formula of H75, an electron transport layer material used in organic solar cells;
[0034] Figure 6 The figure is a JV curve of an organic solar cell made using the oligomeric self-assembled hole transport layer material of the present invention;
[0035] Explanation of the marks in the figure: 1. ITO transparent conductive glass; 2. Hole transport layer; 3. Active layer; 4. Electron transport layer; 5. Metal electrode. DETAILED DESCRIPTION
[0036] In order to better understand the purpose, structure and function of the present invention, the following is a further detailed description of an oligomeric self-assembled hole transport layer material, a preparation method and an application of the present invention in conjunction with the accompanying drawings.
[0037] Example 1
[0038] Synthesis of Dimer-3-1
[0039]
[0040] Step 1) 3-bromocarbazole (984.4 mg, 4 mmol) shown in Formula 1 was added to the reaction flask and dissolved in 20 ml of dimethyl sulfoxide (DMSO), ice-bathed at 0 ° C, then NaH (144 mg) was added and stirred at room temperature for 0.5-1 h. Diethyl (4-bromobutyl) phosphonate (1.747 g, 6.4 mmol) was subsequently added and heated under reflux at 60 ° C for 24 h. After completion of the reaction, the reaction solution was poured into a separatory funnel, extracted with dichloromethane, dried, and the crude product was separated by chromatography using a column eluent of petroleum ether / ethyl acetate (1:1, V / V) to obtain 1.644 g of an oily liquid intermediate 3 with a yield of 93.8%. Intermediate 3 was tested under a nuclear magnetic resonance spectrometer to obtain a chemical shift of hydrogen spectrum:
[0041] 1HNMR(400MHz, CDCl3)δ8.39(d,J=1.8Hz,1H),8.21–8.14(m,1H),7.87–7.75(m,3H),7.54–7.39(m,3H),7.26(s,2H) ,4.37(t,J=7.0Hz,2H),4.12–3.97(m,4H),2.03(dq,J=10.4,4.9Hz,2H),1.83–1.67(m,3H),1.26(t,J=7.1Hz,7H).
[0042] Step 2) Under N2 atmosphere, intermediate 3 (1.644 g, 3.75 mmol) was dissolved in toluene / ethylene glycol dimethyl ether (25 mL each), 1,4-phenylenediboronic acid bis(pinacol) ester (561 mg, 1.70 mmol) was added, tetrakistriphenylphosphine palladium (92 mg) was added as a catalyst, and cesium carbonate (2.215 g) was added. The reaction was stirred for 24 hours at 125°C. After completion of the reaction, the mixture was extracted with dichloromethane, and the crude product was separated by chromatography using petroleum ether / ethyl acetate (2:1, v / v) as the eluent to obtain intermediate 5 (1.268 g, 1.6 mmol) as an oily liquid with a yield of 94.1%. Intermediate 5 was tested under a nuclear magnetic resonance spectrometer, and the chemical shift of the hydrogen spectrum was obtained as follows:
[0043] 1 HNMR(400MHz, CDCl3)δ8.39(d,J=1.8Hz,2H),8.21–8.14(m,2H),7.87–7.75(m,6H),7.54–7.39(m,6H),7.26(s,4H) ,4.37(t,J=7.0Hz,4H),4.12–3.97(m,8H),2.03(dq,J=10.4,4.9Hz,5H),1.83–1.67(m,6H),1.26(t,J=7.1Hz,14H).
[0044] Step 3) Under a nitrogen atmosphere, intermediate 5 (1.268 g, 1.6 mmol) was dissolved in 1,4-dioxane (20 mL), and trimethylsilyl bromide (2.449 mg, 16 mmol) was added dropwise. The reaction was allowed to react at room temperature for 24 h. After completion of the reaction, methanol (10 mL) was added dropwise and stirred at room temperature for 1 h to remove excess trimethylsilyl bromide. Deionized water was then added dropwise until the solution became opaque and a white solid precipitated. Dimer-3-1 was filtered and dried to obtain a white solid (1.004 g, 92.2% yield).
[0045] Dimer-3-1 was tested under a nuclear magnetic resonance spectrometer, and the chemical shift of the hydrogen spectrum was obtained as follows:
[0046] 1 HNMR (400MHz, DMSO) δ8.57(d,J=1.8Hz,2H),8.34–8.26(m,2H),7.92(s,4H),7.86(dd,J=8.5,1.8Hz,2H),7.74(dd,J=8.8,2.3Hz,2H),7.66 (d,J=8.2Hz,2H),7.49(t,J=7.7Hz,2H),7.24(t,J=7.4Hz,2H),4.46(t,J=5.7Hz,5H),1.91(t,J=7.3Hz,5H),1.62(dq,J=33.0,8.6Hz,10H).
[0047] Example 2
[0048] Synthesis of Dimer-3-2:
[0049]
[0050] Step 1) Add 3-bromocarbazole (984.4 mg, 4 mmol) to a reaction flask, dissolve it in 20 ml of N,N-dimethylformamide (DMF), place in an ice bath at 0°C, then add NaH (144 mg) and stir at room temperature for 0.5-1 h. Subsequently, add diethyl (4-bromobutyl) phosphonate (1.747 g, 6.4 mmol) and heat under reflux at 70°C for 12 h. After the reaction is complete, extract with dichloromethane and dry. The crude product is separated by chromatography using petroleum ether / ethyl acetate (1:1, V / V) as the eluent to obtain 1.577 g of an oily liquid product with a yield of 90%. Step 1) is tested under a nuclear magnetic resonance spectrometer, and the chemical shift of the hydrogen spectrum is obtained as follows:
[0051] 1 HNMR(400MHz, CDCl3)δ8.39(d,J=1.8Hz,1H),8.21–8.14(m,1H),7.87–7.75(m,3H),7.54–7.39(m,3H),7.26(s,2H) ,4.37(t,J=7.0Hz,2H),4.12–3.97(m,4H),2.03(dq,J=10.4,4.9Hz,2H),1.83–1.67(m,3H),1.26(t,J=7.1Hz,7H).
[0052] Step 2) Under a nitrogen atmosphere, the product from step 1) (1.577 g, 3.6 mmol) was dissolved in toluene (40 mL). 1,3-phenylenediboronic acid bis(pinacol) ester (475 mg, 1.44 mmol) was added, along with the catalyst di(tri-tert-butylphosphine)palladium (125 mg) and cesium carbonate (2.28 g). The mixture was stirred for 12 h at 110°C. After completion of the reaction, the mixture was extracted with dichloromethane, and the crude product was separated by chromatography using ethyl acetate / methanol (100:1, v / v) as the eluent to obtain an oily liquid product (1.113 g, 1.40 mmol) with a yield of 97%. Intermediate 5 was analyzed by nuclear magnetic resonance spectroscopy, yielding the following chemical shifts:
[0053] 1 HNMR(400MHz, CDCl3)δ8.41(d,J=1.7Hz,2H),8.17(d,J=7.7Hz,2H),8.03(q,J=3.0Hz, 1H),7.82(dd,J=8.5,1.8Hz,2H),7.69(dd,J=7.4,1.8Hz,2H),7.58(dd,J=8.3,6.9Hz, 1H),7.49(dd,J=8.1,6.5Hz,4H),7.42(d,J=8.1Hz,2H),7.26(s,4H),4.37(t,J=7.0Hz ,4H),4.08–3.98(m,8H),2.07–2.00(m,4H),1.80–1.70(m,8H),1.25(t,J=7.0Hz,12H).
[0054] Step 3) Under N2 atmosphere, the product obtained in step 2) (1.113 g, 1.40 mmol) was dissolved in dichloromethane (20 mL), and trimethylsilyl bromide (2.448 g 15.9 mmol) was added dropwise. The reaction was allowed to react at room temperature for 12 h. After the reaction was completed, methanol (10 mL) was added dropwise and stirring was continued for 1 h to remove excess trimethylsilyl bromide, followed by deionized water added dropwise until the solution became opaque and solid precipitated. Filtered and dried to obtain a white solid Dimer-3-2 (837 mg, 87.9% yield). Dimer-3-2 was tested under a nuclear magnetic resonance spectrometer, and the chemical shift of the hydrogen spectrum was obtained as follows:
[0055] 1 HNMR(400MHz,DMSO)δ8.09–7.94(m,4H),7.56–7.24(m,11H),7.12–6.96(m,4H),4.23(d t,J=10.0,4.9Hz,4H),1.70(p,J=7.2Hz,4H),1.58–1.34(m,7H),1.03(t,J=7.0Hz,2H).
[0056] Example 3
[0057] An organic solar cell device was prepared using the oligomeric organic compounds obtained in Examples 1 and 2 as hole transport materials. The device structure is as follows: Figure 1 As shown, from bottom to top, they are: ITO transparent conductive glass is marked as 1, hole transport layer is marked as 2, active layer is marked as 3, electron transport layer is marked as 4, and metal electrode is marked as 5. The structural formulas of the active layer donor material, acceptor material and electron transport layer material are as follows Figure 3-5 As shown, the specific preparation process of the solar cell device is as follows:
[0058] An oligomeric organic compound was used as a hole transport material. A 0.27 mg / ml solution was prepared in ethanol, and 60 μl of the oligomeric organic compound solution was statically coated on ITO transparent conductive glass. (Before static coating, the ITO transparent conductive glass was ultrasonically cleaned three times with detergent and deionized water for 5 minutes each, then ultrasonically cleaned with acetone for 15 minutes, and finally ultrasonically cleaned twice with isopropanol for 15 minutes each, and then irradiated in a UV-ozone machine for 20 minutes.) After annealing at 100°C for 10 minutes, a hole transport layer was formed. A 16 mg / ml active layer solution was prepared by preparing a 12.5 mg / ml DIB solution of PM6:L8-BO in a mass ratio of 1:1.2 using chloroform. This solution was spin-coated on the modified ITO transparent conductive glass and annealed at 100°C for 10 minutes to form an active layer. A 1 mg / ml H75 solution prepared in methanol was then spin-coated to form an electron transport layer. Finally, 100 nm Ag was evaporated as the cathode.
[0059] Example 4
[0060] This embodiment refers to embodiment 3, except that the hole transport layer is replaced with 2PACZ, the structural formula of which is shown in the attached Figure 2 , concentration is 0.27mg / ml.
[0061] Photovoltaic device performance: Under the irradiation of 1.5G (100mWcm-2) white light from a solar simulator, the current density and voltage (JV) characteristic curves of the battery device prepared with Dimer-3-1, Dimer-3-2, and 2PACZ as the hole transport layer are shown in the attached Figure 6 Specific data comparison is shown in Table 1, where Voc represents open circuit voltage, Jsc represents short circuit current, FF represents fill factor, and PCE represents photoelectric conversion efficiency.
[0062] As can be seen from Table 1, the oligomeric organic compound prepared by the present invention is used as the hole transport layer material of the organic solar cell. The strength with the ITO conductive glass can be enhanced through multi-dentate bonding, thereby accelerating the hole transport rate. This is manifested in that the Voc, Jsc, and FF values of the prepared optoelectronic functional device are higher, and the PCE performance is significantly improved.
[0063]
[0064] Table 1
[0065] It will be understood that the present invention is described by way of some embodiments, and it will be appreciated by those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are intended to be protected by the present invention.
Claims
1. An oligomeric self-assembled hole transport layer material, characterized in that: The invention comprises an oligomeric organic compound having the general structure of formula (I) or formula (II): In formula (I) and formula (II), n is an integer selected from 0 to 5, and R is a structure including an aromatic group.
2. The oligomeric self-assembled hole transport layer material according to claim 1, characterized in that: The R is one of the following three general structures:
3. The method for preparing an oligomeric self-assembled hole transport layer material according to claim 1, wherein: The following steps are involved: 1) Under inert gas protection, 3-halogen carbazole is dissolved in an organic solvent, ice-bathed at 0°C, and then NaH is added. Then, a phosphonate with a halogen end group is added, and the mixture is heated under reflux. After extraction and column chromatography, a solid product is obtained; 2) Under inert gas protection and in an alkaline environment, mixing the product obtained in step 1) with an aryl borate, adding an organic solvent and a catalyst, heating under reflux to perform a Suzuki coupling reaction, and obtaining a carbazole phosphonate benzene derivative through extraction and column chromatography; 3) Under inert gas protection, dissolving the product obtained in step 2) in an organic solvent, adding trimethylsilyl bromide to react at room temperature, quenching with alcohol, and then precipitating with a poor solvent. The precipitated solid is filtered to obtain the oligomeric self-assembled hole transport layer material.
4. The method for preparing an oligomeric self-assembled hole transport layer material according to claim 3, characterized in that: In step 1), the molar ratio of 3-halogen carbazole to phosphonate with a halogen terminal group is 1:1 to 3; and / or, in step 1, the molar ratio of 3-halogen carbazole to NaH is 1:1 to 3; And / or, in step 1, the reaction temperature of heating under reflux is 60° C. to 100° C., and the reaction time is 12 to 24 hours.
5. The method for preparing an oligomeric self-assembled hole transport layer material according to claim 3, characterized in that: In step 2, the molar ratio of the product obtained in step 1 to the aryl borate is 2 to 4:1; And / or, in step 2, the reaction temperature of heating under reflux is 110° C. to 125° C., and the reaction time is 12 to 24 hours.
6. The method for preparing an oligomeric self-assembled hole transport layer material according to claim 3, characterized in that: In step 3, the molar ratio of the product obtained in step 2 to trimethylsilyl bromide is 1:5-1:100; And / or, in step 3, the reaction temperature is room temperature and the reaction time is 12 to 24 hours.
7. Use of an oligomeric self-assembled hole transport layer material according to claim 1 in preparing a photoelectric functional device, characterized in that: The optoelectronic functional device is an organic solar cell.
8. Use of an oligomeric self-assembled hole transport layer material according to claim 7 in the preparation of optoelectronic functional devices, characterized in that: The structure of the organic solar cell device is as follows from bottom to top: ITO transparent conductive glass, hole transport layer, active layer, electron transport layer, metal electrode, and the hole transport layer includes the oligomeric self-assembled hole transport layer material.